Polymer-functionalized mesoporous carbon nanoparticles on overcoming multiple barriers and improving oral bioavailability of Probucol. (1st February 2020) - Lu, Hongyan; Yang, Guangzhao; Ran, Fu; Gao, Tianbin; Sun, Changshan; Zhao, Qinfu; Wang, Siling
Graphical abstract: Highlights: Polymer-modified MCNs to overcome mucous and epithelial barriers is rarely reported. Cellular uptake of MCNs is quantified by UV spectrophotometry. Polymer-modified MCNs could trace the MCNs in vivo and control the drug release. Abstract: Oral administration of nanoparticles is extremely limited due to the two processes of mucus permeation and epithelial absorption, which requires completely opposite surface properties of the nanocarriers. To tackle the contradiction, we developed a rational strategy to modify the surface of mesoporous carbon nanoparticles with chitosan concealed by a hydrophilic N-(2-hydroxypropyl) methacrylamide copolymer (pHPMA) layer. Probucol (PB) with the low poor permeability and solubility was loaded in optimal nanocarriers to realize the high loading efficacy and controlled release. The pHPMA polymer is a hydrophilic "mucus-inert" material, which could be dissociable from the surface of nanoparticles in the mucus, thus promoting their mucus permeation and causing exposure of chitosan in transepithelial transport. The swelling effect of chitosan under acidic conditions allowed regulation of PB release behavior. In conclusion, the mucus-permeable nanocarrier could effectively overcome multiple gastrointestinal absorption barriers and the oral bioavailability of PB-loaded HCMCN was 2.76-fold that of commercial preparation.